Interaction between the microbiota and the skin barrier in aging skin: a comprehensive review - Woo, Yu Ri; Kim, Hei Sung (Frontiers in Physiology, 2024)
The interplay between the microbes and the skin barrier holds pivotal significance in skin health and aging. The skin and gut, both of which are critical immune and neuroendocrine system, harbor microbes that are kept in balance. Microbial shifts are seen with aging and may accelerate age-related skin changes. This comprehensive review investigates the intricate connection between microbe dynamics, skin barrier, and the aging process. The gut microbe plays essential roles in the human body, safeguarding the host, modulating metabolism, and shaping immunity. Aging can perturb the gut microbiome which in turn accentuates inflammaging by further promoting senescent cell accumulation and compromising the host's immune response. Skin microbiota diligently upholds the epidermal barrier, adeptly fending off pathogens. The aging skin encompasses alterations in the stratum corneum structure and lipid content, which negatively impact the skin's barrier function with decreased moisture retention and increased vulnerability to infection. Efficacious restoration of the skin barrier and dysbiosis with strategic integration of acidic cleansers, emollients with optimal lipid composition, antioxidants, and judicious photoprotection may be a proactive approach to aging. Furthermore, modulation of the gut-skin axis through probiotics, prebiotics, and postbiotics emerges as a promising avenue to enhance skin health as studies have substantiated their efficacy in enhancing hydration, reducing wrinkles, and fortifying barrier integrity. In summary, the intricate interplay between microbes and skin barrier function is intrinsically woven into the tapestry of aging. Sound understanding of these interactions, coupled with strategic interventions aimed at recalibrating the microbiota and barrier equilibrium, holds the potential to ameliorate skin aging. Further in-depth studies are necessary to better understand skin-aging and develop targeted strategies for successful aging.